Occurrence of diversity in dental pattern and their role in identification in Udaipur population: an orthopantomogram based study - Metgud, Rashmi; Bhardwaj, Tina; Naik, Smitha; Tak, Aniruddh (International Journal of Dental Research, 2016)
Background: Dental comparison is based on unique characteristics of the teeth (shape and outline, restorations, supernumerary teeth, impacted, fractured teeth etc.). Being the hardest structure in human body, teeth represent an ideal means of identification in situations of advanced decomposition, fire and mass disaster. Orthopantomogram is a broadly applied standard method in today’s practical dentistry and provides a complete view of the teeth and both jaws in one image.AIM: The present study aimed to verify the diversity of dental patterns in Udaipur population based on specific patterns of missing, filled, unrestored (virgin) and impacted teeth using Orthopantomogram.Material and Methods: 300 Dental Orthopantomogram were randomly selected from Pacific Dental College & Hospital, Udaipur and observed for the occurrence of dental patterns. The frequency of occurrence of dental patterns and the diversity in dental patterns were calculated for full dentition, maxilla and mandible.Results: Occurrence of most common dental pattern was formed by 32 virgin teeth, 10.66%. the diversity of dental pattern for full dentition was 99.7%, maxilla was 99.5%, and mandible was 99.49%.Conclusion: The diversity derived from dental patterns is a potentially valuable tool with broad applicability for human identification inspite of the mentioned drawbacks.